(untitled) (International Journal of Physiotherapy, 2020)
Background: Fear-Avoidance Beliefs Questionnaire (FABQ), Quebec Back Pain Disability Scale (QDS), and Roland-Morris Disability Questionnaire (RMDQ) is widely used in patients with low back pain (LBP) to assess the level of disability. Nonetheless, there are limited data about the responsiveness properties of the Arabic versions of these scales. This study was conducted to assess the responsiveness of the Arabic versions of the FABQ, QDS, and RMDQ compared to that of the Visual Analog Scale (VAS). Methods: A sample of 68 patients with LBP completed FABQ, QDS, RMDQ, and VAS at baseline and after 14 days. Responsiveness was evaluated by calculating the standard error of measurement (SEM), the minimal detectable difference at 95% confidence level (MDD95%), standardized response mean (SRM), Cohen’s effect size (ES), Guyatt’s responsiveness index (GRI), area under the curve (AUC), and minimal clinically significant difference (MCID). Results: The SEM, MDD 95%, SRM, ES, GRI, AUC, and MCID for FABQ, QDS, RMDQ, and VAS were 2.54, 2.83, 0.77, and 0.82; 7.05, 7.85, 2.14, and 2.28; 0.67, 0.96, 0.74, and 1.04; 0.39, 0.39, 0.36, and 0.79; 0.76, 1.34, 1.26, and 1.66; 0.49, 0.63, 0.57, and 0.70; and 3.5, 4.5, 2.5, and 1.5; respectively. Conclusion: Although the responsiveness of the Arabic versions of FABQ, QDS, and RMDQ was below the recommended standards and less than the responsiveness calculated for the VAS, it was comparable with previously published versions in other languages. Additional studies are necessary to examine the three scales’ responsiveness with a more extended follow-up period.